Assessment of Patients with Coronary Artery Diseases Need to Discharge Plan regarding to Living and Home Arrangement at Babylon Teaching Hospitals - Kareem Waheed Mohamed (Journal of Global Pharma Technology, 2018)
Background: Coronary artery disease is one of the most serious diseases affecting human health, leading to more disability, economic cost and death (Hussein. 2014). Implementing the discharge plan from the health personals in the hospital correctly is to reduce the patient's long stay in the hospital also to improve the coordination of services after the discharge to home and reduce the frequency of admission to the hospital (Shepperd, ET .al. 2013). Objective: To assess the needs of patients with coronary artery disease for discharge plan related to living arrangement and home activities. Method and Results: Descriptive- cross sectional design selected to carry out this study, two Babylon Teaching Hospitals used to collect the study from the period between 1 Sep. 2016 to 1 Sep. 2017.Non- probability purposive sample of (100) patients who admitted to the Coronary Care units or medical ward were selected to participated in the study. Special questionnaire prepared after comprehensive literature review, face-to-face interview used as a method to collect the data. The statistical results shows that the majority (65%) of the study sample were male, (64%)were 60 or above 60 years old, (41%) were illiterate, most of the sample (34%) were retired, related to the living arrangement and home activities they recorded poor responses regarding most items. Conclusion: Significant need poor related to home and living arrangement discharge plan for patients with coronary artery disease. Which need health team intervention? Poor responses recorded by the patients with coronary artery disease, significant need to structured discharge plan related to living arrangement and home activities clearly appears. Significant need, poor responses recorded by the patient with coronary artery disease related living and home arrangement. Recommendation: Special discharge plan may take place to cover the patients need and increase their knowledge related to the home activities and living arrangement, which enhance life style and reduce expected complication.Keywords: Discharge plan, Coronary artery disease, Living and home arrangement.